Hypofractionated radiotherapy with simultaneous integrated boost for localized prostate cancer patients: effects on immune system and prediction of toxicity - D’Auria, Fiorella; Valvano, Luciana; Calice, Giovanni; D’Esposito, Vittoria; Cabaro, Serena; Formisano, Pietro; Bianchino, Gabriella; Traficante, Antonio; Bianculli, Antonella; Lazzari, Grazia; Statuto, Teodora; Rago, Luciana (Frontiers in Immunology, 2024)
Background. The other side of radiotherapy (RT), in addition to the cytotoxic effect, is the ability to modulate the immune system in terms of activation or suppression, also depending on the dose and fractionation delivered. This immune RT effect can be detected both locally in the irradiated tumor site and in the peripheral blood. The aim of this study was to assess the consequence of pelvic irradiation on peripheral immune cells and cytokine secretions in localized prostate cancer (PC) patients undergoing pelvic irradiation with a simultaneous moderately hypofractionated prostate/prostate bed boost by Volumetric Modulated Arc Therapy (VMAT). Furthermore, we analyzed whether there was a correlation between these peripheral immune parameters and acute and late genitourinary (GU) and gastrointestinal (GI) toxicity. Methods. Thirty-eight PC patients were treated with pelvis irradiation (dose per fraction 1.8 Gy) and simultaneous hypofractionated (median dose per fraction: 2.7 Gy) prostate/prostate bed boost. Longitudinal analysis was performed for 12 months on peripheral blood to assess changes in 9 different lymphocyte subpopulations by flow cytometry and 10 circulating cytokines by Multiplex Luminex assay and ELISA. Results. Our analysis revealed that basal IFN-γ serum values were significantly lower in definitive (curative intent for patients with prostate) patient group respect to post-operative one. All the lymphocyte subsets and IFN-α, IFN-β and Il-2 peripheral concentrations displayed significant variations between the different time points considered. The immune cell population that suffers the greatest RT toxicity in the blood was B lymphocyte. We found an interesting correlation between basal TGF-β1 and late GU toxicity. In particular, TGF-β1 concentrations before RT were significantly higher in patients that experienced grade 2-3 of late GU toxicity, respect to grade 0-1. Exploring possible correlations between some clinical/biological findings and radiation planning parameters, we found no statistical significance. Conclusions. Our study analyzed, in the context of hypofractionated radiotherapy in prostate cancer, different parameters of the peripheral immune system. We have highlighted longitudinally the behavior of different lymphocyte subpopulations and of 10 cytokines during the first year after RT. One of the analyzed cytokines, such as TGF-β1, have proven to be promising predictive factor of severe late GU toxicity.